Relevansi Pendidikan terhadap Kinerja Pejabat Pemerintahan Propinsi Sumatera Barat - Yunus, Yasril (Jurnal Demokrasi, 2003)
The objective of this study is to find whether the educational background of official government at West Sumatra Provincial Office is relevant to their job. Data is analyzed by using statistical description with percentage, rate, and deviation standard. The study indicated that there is no significant relevance of formal and informal educational background of the government official of West Sumatra province to support their job. To make it relevant, it needs conducting meritocration, reviewing curriculum of in-service training,Â  selecting and improving the trainers and learning strategies. Â  Kata kunci: relevansi, pendidikan dan kinerja pejabat